Hospitalists' guide to the care of older patients - Williams, Brent (Brent C.); Malani, Preeti N.; Wesorick, David H. (Hoboken, New Jersey : Society of Hospital Medicine/Wiley, 2014)
"Providing a practical, up-to-date reference in Geriatric Medicine, Hospitalists' Guide to the Care of Older Patients is the first book written specifically for hospitalists who need concise, evidence-based information on the vital topic of caring for older hospitalized patients. This groundbreaking text covers the care of older patients, their needs and vulnerabilities, and the current hospital practice environment. The book provides tools to translate what is known about the older patient's unique needs into steps that can be immediately implemented to improve care and limit avoidable morbidity"--Provided by publisher.
Includes bibliographical references.
Description based on print version record and CIP data provided by publisher.
Keywords: Geriatrics; Older people -- Hospital care; MEDICAL -- Gynecology & Obstetrics; Geriatrics; Older people -- Hospital care; Geriatrics; Hospitalization; Aged; Electronic books; Electronic books